Predicting the need for cerebrospinal fluid shunt implantation after spontaneous intracerebral hemorrhage: a challenging task - Khalaveh, Farjad; Zeiser, Vitalij; Cho, Anna; Schmelzer, Sophie; Reinprecht, Andrea; Herta, Johannes; Roessler, Karl; Dorfer, Christian (Frontiers in Neurology, 2023)
OBJECTIVES The development of persistent hydrocephalus in patients after spontaneous intracerebral hemorrhage (ICH) is still poorly understood and many variables predicting the need for a cerebrospinal fluid (CSF)-shunt have been described in the literature with varying results. The aim of this study is to find predictive factors for shunt dependency. METHODS We performed a retrospective, single-center study of 99 neurosurgically treated patients with spontaneous ICH. Variables, including age, Glasgow Coma Scale (GCS), intraventricular hemorrhage (IVH), location of hemorrhage, acute hydrocephalus and volumetric analysis of IVH, ICH and intraventricular CSF were compared between patients with and without CSF-shunt implantation. Furthermore, receiver operating characteristics (ROC) for ICH, IVH and intraventricular CSF volume parameters were calculated. RESULTS CSF-shunt implantation was performed significantly more often in patients after thalamic (p=0.03) and cerebellar ICH (p=0.04). Moreover, a lower ratio between the total hemorrhage volume and intraventricular CSF volume (p=0.007), a higher IVH distribution in the third ventricle and an acute hydrocephalus (p<0.001) with an increased intraventricular CSF volume (p<0.001) were associated with shunt dependency. Our ROC model demonstrated a sensitivity of 82% and a specificity of 65% to predict the necessity for a shunt at a cutoff-value of 1.9 with an AUC of 0.835. CONCLUSIONS Volumetric analysis of ICH, IVH and intraventricular CSF may improve the prediction of CSF shunt implantation in patients with spontaneous ICH.